REAL ESTATE MANAGEMENT SYSTEM - Deepika S.; Jeyabharathi G.; Mrs. S.Kulandai Teresa (Galaxy International Interdisciplinary Research Journal, 2022)
The project title is real estate management system this web application helps the user to register an individual home or apartment to assist you in finding the perfect rental home or property also you can find your next rental from the search view in your targeted area the features of the real estate management system are that the admin can manage a house by entering details such as house number features rent status and review to add tenants the user has to enter the full name gender national id phone number email id registration date house agreement document status and exit date besides the admin can also add the invoice and payments too the front end of the application is PHP and the back end of the application is my SQL